The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/healthcare10122508
|View full text |Cite
|
Sign up to set email alerts
|

Association between Nutrition Literacy and Bangladeshi Adults’ Healthy Eating Behaviors: Evidence from the Nutrition Literacy Study 2021

Abstract: This study investigated the association between healthy eating behaviors and nutrition literacy in a sample of Bangladeshi adults. A cross-sectional survey was conducted among 400 adults from two districts of Bangladesh (Dhaka and Chattogram). Data were generated by in-person interviews using a structured questionnaire. The Nutrition Literacy Scale and National Dietary Guidelines for Bangladesh were used to assess nutrition literacy and healthy eating behaviors, respectively. Multiple linear regression models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…34 We designed a semistructured questionnaire (online supplemental file 2) for our research, drawing on previous studies and relevant literature. This questionnaire aimed to gather demographic information from participants, assess dietary behaviours based on established research 35 and camp experiences and investigate food preferences by incorporating insights from the literature 36 and camp-related experiences. Additionally, we included select questions to gather data on camp rations, considering factors such as availability, accessibility and price, with reference to existing literature, 1 37 camp experiences and press releases.…”
Section: Study Population and Samplementioning
confidence: 99%
“…34 We designed a semistructured questionnaire (online supplemental file 2) for our research, drawing on previous studies and relevant literature. This questionnaire aimed to gather demographic information from participants, assess dietary behaviours based on established research 35 and camp experiences and investigate food preferences by incorporating insights from the literature 36 and camp-related experiences. Additionally, we included select questions to gather data on camp rations, considering factors such as availability, accessibility and price, with reference to existing literature, 1 37 camp experiences and press releases.…”
Section: Study Population and Samplementioning
confidence: 99%
“…This concept is based on the idea that everyone should have fair access to the same types of quality nutrition, regardless of their circumstances. Al Banna and colleagues [ 11 ] investigated the association between nutrition literacy and healthy eating behaviors among Bangladeshi adults. The authors observed a positive relationship between healthy eating behavior and nutrition literacy.…”
Section: Nutrition Equitabilitymentioning
confidence: 99%